Cabozantinib for patients with advanced hepatocellular carcinoma: a cost-effectiveness analysis - Amir Shlomai; Moshe Leshno; Daniel A. Goldstein (Therapeutic Advances in Gastroenterology, 2019)
Background and aims: The multi-kinase inhibitor sorafenib is a first-line drug for patients with advanced hepatocellular carcinoma (HCC). Treatment options for patients whose disease has progressed on sorafenib are limited. In a recent randomized controlled trial (CELESTIAL trial), patients with advanced HCC who had failed prior systemic therapy had moderate progression-free survival and overall survival advantages when treated with the multi-kinase inhibitor cabozantinib. However, since this treatment is costly and is accompanied by significant adverse events in a large proportion of patients, its cost-effectiveness in these patients should be determined. Methods: We developed a Markov model incorporating health outcomes, measured by life-years and quality-adjusted life-years (QALYs) to evaluate the cost-effectiveness of cabozantinib compared with placebo in patients who have failed prior systemic therapy. Results: Treatment with cabozantinib results in a mean gain of 11.6 weeks of life (0.22 life-years) as compared with placebo. When quality of life was incorporated, treatment with cabozantinib produced a gain of 0.16 QALYs. The total mean incremental cost of cabozantinib was US$76,406 per patient. The incremental cost-effectiveness ratio for cabozantinib compared with best supportive care was US$469,374/QALY using the recommended dose of 60 mg cabozantinib daily. Conclusion: Our results suggest that the use of cabozantinib in patients with advanced HCC who have progressed on prior treatment, results in a modest incremental benefit with high incremental costs, suggesting that it is not cost-effective at conventional willingness to pay thresholds.